The Paradox Between Political Islam and Islamic Political Parties: The Case of West Sumatera Province - Wanto, Adri (Al-Jamiah Research Centre, 2012)
The aim of this paper is to explain the apparent paradox between political Islam and Islamic political parties in Indonesia. On one hand, the support for Islamic political parties is in decline, while, on the other religious intolerance and the implementation of local regulations based on the shariâah laws have increased in many provinces. This paper argues that political Islam and Islamic political parties are not synonymous. Moreover, the aim of achieving an ideal society according to an Islamistâs vision and their religious interpretations does not only by adopt a top-down strategic model through participation in formal politics but also by using bottom-up strategic model by focusing on the societal level. By adopting gradualist approaches, hardliner Islamist ideas disseminate peacefully in Indonesia today. This study will focus on West-Sumatra as a case study, considering West Sumatra is one of the most widely province issued the shariâah laws in Indonesia. This article will shed light on local and often underestimated dynamics.[Artikel ini menjelaskan paradoks antara Islam politik dan partai politik Islam di Indonesia. Jika pada satu sisi, dukungan terhadap partai politik Islam menurun, namun pada sisi berbeda tingkat intoleransi dan angka peraturan daerah berbasiskan syariah meningkat. Karena itu, artikel ini berargumen bahwa Islam politik dan partai politik Islam tidak selalu sejalan. Selain itu, cita-cita untuk mewujudkan masyarakat yang Islami tidak melulu harus diwujudkan dari atas-ke-bawah melalui partisipasi politik, namun juga dari bawah-ke-atas, yakni menitikberatkan pada level masyarakat. Dengan strategi gradual -perlahan-lahan-, gagasan fundamentalis Islam tanpa sadar telah menginfiltrasi. Artikel ini menjelaskan Sumatra Barat sebagai studi kasus persoalan di atas. Pilihan Sumatra Barat berdasarkan pada realitas bahwa di propinsi inilah, perda shariâah paling banyak diberlakukan. Artikel ini akan berkontribusi pada diskusi mengenai politik lokal dan dinamikanya.]